2014
DOI: 10.1002/jhm.2261
|View full text |Cite
|
Sign up to set email alerts
|

Quality and safety during the off hours in medicine units: A mixed methods study of front‐line provider perspectives

Abstract: BACKGROUND Hospital off‐hours care is associated with poor outcomes. Mutual conceptualization among provider groups may facilitate improvement efforts. Provider‐perceived threats to quality are unreported. OBJECTIVES The objectives of this study were to identify perceived off‐hours quality and safety issues, assess the most significant, and evaluate differences between nurses, and attending and housestaff physicians, and providers with day and night experience. DESIGN Prospective, sequential, exploratory mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Communication breakdowns between interprofessional team members (eg, physicians and nurses 10,58 or primary and consulting services 59,60 ) may occur as the day progresses and be transmitted to parents. 52,61,62…”
Section: Discussionmentioning
confidence: 99%
“…Communication breakdowns between interprofessional team members (eg, physicians and nurses 10,58 or primary and consulting services 59,60 ) may occur as the day progresses and be transmitted to parents. 52,61,62…”
Section: Discussionmentioning
confidence: 99%
“…This represents a lost opportunity for parents to serve as key partners in ensuring the safety and quality of hospital care. This may be particularly true at night, when parents are often at their children’s bedside and hospitals typically have decreased staffing 5,6,29 and busier providers who may not know patients as well. 9,30 In addition to affecting safety, lack of shared understanding at night may affect parent experience because communication with nighttime providers is associated with overall parent experience of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Many studies have documented challenges in communication or collaboration between physicians and nurses in this process; however, these barriers remain in clinical practice. [11][12][13] In addition, a previous scoping review regarding nighttime detection and response to clinical deterioration identified a gap in research concerning nighttime interprofessional communication and collaboration in response to deteriorating patients. 14 Accordingly, knowledge development that focuses on nighttime interprofessional collaboration may help address the challenges of responding to clinical deterioration at night.…”
Section: Introductionmentioning
confidence: 99%